From film practice to critical and analytical practice. Independent and activist cinema in the film press from late Francoism to the transition to democracy (1967-1978) - Nieto Ferrando, Jorge (Estudios sobre el Mensaje Periodístico, 2018)
The independent cinema produced in Spain in late Francoism and during the period of the transition to democracy was accompanied by an important reflection on its nature, type and function. From a selection of representative periodical publications, this article aims to analyze the issues that are focused on in this reflection: amateur cinema, possibilism, political cinema in Latin America and France, the so-called “cinema of nationalities", activist cinema and the new trends in thinking and in film criticism. The effect of these reflections is also noticeable in the production of independent cinema, particularly activist cinema.